Rethinking the Other in Antiquity - Gruen, Erich S. (Book collections on Project MUSE., 2011)
Prevalent among classicists today is the notion that Greeks, Romans, and Jews enhanced their own self-perception by contrasting themselves with the so-called Other--Egyptians, Phoenicians, Ethiopians, Gauls, and other foreigners--frequently through hostile stereotypes, distortions, and caricature. In this provocative book, Erich Gruen demonstrates how the ancients found connections rather than contrasts, how they expressed admiration for the achievements and principles of other societies, and how they discerned--and even invented--kinship relations and shared roots with diverse peoples. Gruen shows how the ancients incorporated the traditions of foreign nations, and imagined blood ties and associations with distant cultures through myth, legend, and fictive histories. He looks at a host of creative tales, including those describing the founding of Thebes by the Phoenician Cadmus, Rom's embrace of Trjoan and Arcadian origins, and Abraham as ancestor to the Spartans. Gruen gives in-depth readings of major texts by Aeschylus, Herodotus, Xenophon, Plutarch, Julius Caesar, Tacitus, and others, in addition to portions of the Hebrew Bible, revealing how they offer richly nuanced portraits of the alien that go well beyond stereotypes and caricature.